(untitled) (TAMADDUN NURI JURNALI, 2024)
This article examines the small epic genres of Uzbek folklore, which serve to convey information to the listener.The author puts forward new scientific and theoretical conclusions about “rumors", a modern informative genre ignored by folklore science.